Antishudder Performance of Low-Molecular-Weight Alkenylsuccinimides - Hiroaki Koshima (Japanese Society of Tribologists, 2008)
Addition of excess antishudder additive to transmission oil results in a decrease of the friction coefficient to a level below which the transmission torque capacity becomes unsatisfactory. However, very low concentrations of antishudder additive can result in unsatisfactory antishudder performance and durability. To obtain the optimal balance between antishudder performance and torque capacity, a specific alkenylsuccinimide has been developed. The relationship between the antishudder performance and torque capacity was investigated by performing a series of low-velocity friction apparatus (LVFA) rig tests as well as statistical analysis using the quantitative structure-property relationship (QSPR) method that related the structure and physical properties of the molecule to the measured frictional properties.